The Influence Of Food Safety, Product Availability and Loyalty Program On Repurchase Intention and its Implications On Company Image (a Survey On Customers Of Cv. Torani Sumber Makmur Processed Fish Stall In West Java Region) - Andriyani Saputra; Kartawan Kartawan; Yusuf Abdullah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The objective of this research was to identify and analyze the implications of the influence of food safety, product availability, and loyalty program on repurchase intention and its implications on the company image of CV. Torani Sumber Makmur Processed Fish Stall in the West Java Region. The method used in this research was a survey with a quantitative descriptive approach. The sample size in this research was 187 respondents determined using cluster sampling. By utilizing Partial Least Square-Structural Equation Model (PLS-SEM), the research found that product availability and loyalty program had a significant positive influence on repurchase intention. Meanwhile, food safety had a significant negative influence on repurchase intention. Food safety, product availability, and loyalty program had a significant positive influence on the company image. Repurchase intention had a positive and significant implication on the company image. The influence of product availability and loyalty program on repurchase intention had significant implications on the company image. Whereas, the influence of food safety on repurchase intention did not have significant implications on the company image.